Qur’anic Edu-Theology as a Framework for Holistic Education: A Critical Examination of Pedagogical Values in Surah al-Fātiḥah - Muh Syaifudin; Muhammad Adam; Abdullah Affandi (QOF, 2025)
Within the context of Islamic education, Surah al-Fātiḥah holds potential as a foundation for holistic pedagogy that integrates spiritual, moral, and intellectual dimensions. Nevertheless, empirical research systematically examining the application of Qur’anic Edu-Theology principles in modern educational practices remains limited, creating a gap between normative Qur’anic frameworks and contemporary pedagogical implementation. This study employs a qualitative approach by combining taḥlīlī exegesis for key-term analysis with mawḍū‘ī exegesis for thematic understanding of Surah al-Fātiḥah, integrated with modern educational theories such as compassion-based pedagogy, character education, and behaviorism. The study highlights six core principles of Qur’anic Edu-Theology: (1) divine compassion, (2) inclusivity, (3) justice and moral accountability, (4) loyalty and exemplary conduct, (5) consistency and perseverance, and (6) learning from exemplary models while avoiding misguidance, which can serve as practical guidelines in modern education. The findings indicate that these principles can form a pedagogical framework that is humanistic, transformative, and value-oriented, while simultaneously necessitating adaptive strategies to address normative challenges, including technology integration, student-centered approaches, and project-based learning. The primary contribution of this study is the introduction of the Qur’anic Edu-Theology concept as a paradigm for holistic education relevant to the modern context, while also providing a conceptual foundation for further research to explore other surahs and empirically test their effectiveness in educational practice